2013
DOI: 10.1007/s10926-013-9443-z
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Work Restriction in Employed Adults with Lower Limb Joint Pain: Individual Factors and Area-Level Socioeconomic Conditions

Abstract: Purpose To examine individual and area-level socioeconomic factors that predict the onset of work restriction in employed persons with lower limb joint pain. Methods Population-based prospective cohort study. Adults were aged 50–59, reported hip, knee, foot pain or a combination and maintained employment through 3 year follow-up (n = 716). Work restriction was measured as inability to participate in work as desired. Multi-level logistic regression was used to assess the associations of work restriction onset w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…For the entire study sample of senior workers, we found a significant dose-response association ( p < 0.0001) between leg pain intensity and work-limiting pain. Our results thus elaborate on previous findings demonstrating the importance of not just the presence of pain but also the severity of pain and functional limitation for long-term sickness absence and the ability to work [ 8 , 9 , 14 , 40 ]. For instance, we have previously demonstrated strong dose-response associations of increasing pain intensities in the low-back, neck-shoulders, and knees with increased risk of long-term sickness absence in healthcare workers [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…For the entire study sample of senior workers, we found a significant dose-response association ( p < 0.0001) between leg pain intensity and work-limiting pain. Our results thus elaborate on previous findings demonstrating the importance of not just the presence of pain but also the severity of pain and functional limitation for long-term sickness absence and the ability to work [ 8 , 9 , 14 , 40 ]. For instance, we have previously demonstrated strong dose-response associations of increasing pain intensities in the low-back, neck-shoulders, and knees with increased risk of long-term sickness absence in healthcare workers [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…≥3 on a scale from 0 to 9) compared to low-back and neck−/shoulder pain (5 and 4, respectively) [ 14 ], potentially indicating a relatively larger impact of knee pain on working functional capacity compared to low-back and neck−/shoulder MSDs. This study and others [ 8 , 9 , 40 ] underline the importance of pain intensity on the degree of functional limitation, with higher pain intensities being associated with higher risks of work disability and sickness absence.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…In addition, overall pain levels, illness perceptions and health beliefs have not been included, which may have considerable impact on predicted work outcomes 35. We chose to measure the extent of pain rather than the pain level, as we have previously found extent of pain to be associated with poor work outcomes, and this may be more reflective of total arthritis impact on physical function than pain intensity 36. However, clinical measures may not be as important in predicting work disability, compared with measure of function, psychosocial and workplace factors 34.…”
Section: Discussionmentioning
confidence: 99%